Step-by-Step Illustrated Endoscopic Extraperitoneal Radical Prostatectomy (EERP): Tips and Tricks to Trifecta Outcomes - Reis, Leonardo Oliveira; Starling, Eduardo S.; Pompeo, Antonio C. L.; dos Reis, Rodolfo B.; Nogueira, Lucas; Faria, Eliney F.; Carvalhal, Gustavo F.; Tobias-Machado, Marcos (Urology Journal, 2014)